A framework for deriving dispatching rules of integrated urban drainage systems. (15th November 2021) - Sun, Yan; Hu, Xinchen; Li, Yu; Peng, Yong; Yu, Yanqiu
Abstract: The urban drainage system (UDS) with the integration of new and old, green and gray infrastructures has become an underlying trend, but its sewage dispatch is getting more and more difficult owing to complex network topology, much uncertainty introduced by the lack of empirical data or monitoring system, and consideration of multiple objectives. We propose a novel framework for deriving dispatching rules that allocate the wastewater inflow according to the comprehensive capacity of treatment facilities. The main innovative point of the framework is using the Prophet algorithm to handle sewage volume uncertainty introduced by rainfall. Moreover, we construct a multi-objective optimization model of operating costs and surface water quality and apply it in multiple scenarios. Lastly, we build a decision tree to mine dispatching rules and threshold identification. Taking the Pingshan River Basin, we plot dispatching diagrams and discover the threshold of creating the risk to surface water quality. When the sewage volume reached 18.0 × 10 5 m³ in winter, water quality exceeded limits. Other than that, the wastewater spatiotemporal allocation placed receiving water quality and operating cost in a competitive relationship. An application of dispatching rules shows that they fill a gap in the scientific and reasonable dispatch of the UDS. Highlights: A framework is presented for deriving dispatching rules of integrated urban drainage systems. Uncertainties about the wastewater volume and wetland purification efficiency are considered. The Prophet model extracts the drought flow and its uncertainty range from combined sewage flow. The wastewater spatiotemporal allocation determines competition of the operating costs and surface water quality.